2020
DOI: 10.3390/dairy1010003
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cow Health and Greenhouse Gas Emission Intensity

Abstract: The purpose of this review is to identify the main influencing factors related to dairy cow health as it impacts the intensity of greenhouse gas emissions considering known data presented in the literature. For this study, we define the emission intensity as CO2 equivalents per kilogram of milk. In dairy cows, a high dry matter (DM) intake (25 kg/d) leads to an higher absolute methane emission compared to a lower DM intake (10 kg/d). However, the emission intensity is decreased at a high performance level. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…These include breeding low-CH 4 –emitting animals and improving animal health. However, modeling studies have shown that strategies that improve animal health may significantly increase AP and reduce CH 4 I ( 24 ). In the subsequent section, the effects of mitigation strategies are reported in parenthesis as mean, 95% CI, and the number of treatment comparisons ( n ).…”
Section: Resultsmentioning
confidence: 99%
“…These include breeding low-CH 4 –emitting animals and improving animal health. However, modeling studies have shown that strategies that improve animal health may significantly increase AP and reduce CH 4 I ( 24 ). In the subsequent section, the effects of mitigation strategies are reported in parenthesis as mean, 95% CI, and the number of treatment comparisons ( n ).…”
Section: Resultsmentioning
confidence: 99%
“…These include breeding low-CH4 emitting animals and improving animal health. Modeling studies have shown that strategies that improve animal health can significantly increase animal productivity and reduce emission intensity 16 . In the subsequent text, the effects of mitigation strategies on CH4 emissions and animal performance metrics are reported in parenthesis as mean, 95% confidence interval (CI), and number of treatment comparisons (n).…”
Section: Resultsmentioning
confidence: 99%
“…With relevance to climate change, compromised yields exacerbate levels of greenhouse gas generation per litre of milk produced, 7 while reductions in clinical and subclinical mastitis would reduce CO 2 -equivalent emissions per cow and per kilogram of milk solids produced. 8,9 Therefore, reducing mastitis incidence in the national herd would benefit all stakeholders in the dairy industry and the public good.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of disease is an effective contributor to avoid antibiotic use, promoted by many national and international bodies, for example, the British Veterinary Association, the Responsible Use of Medicines in Agriculture Alliance and the National Mastitis Council. With relevance to climate change, compromised yields exacerbate levels of greenhouse gas generation per litre of milk produced, 7 while reductions in clinical and subclinical mastitis would reduce CO 2 ‐equivalent emissions per cow and per kilogram of milk solids produced 8,9 . Therefore, reducing mastitis incidence in the national herd would benefit all stakeholders in the dairy industry and the public good.…”
Section: Introductionmentioning
confidence: 99%